2003
DOI: 10.1021/ic034691m
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Luminescence Lifetimes of Mononuclear Ruthenium(II)−Terpyridine Complexes by Manipulation of the σ-Donor Strength of Ligands

Abstract: The synthesis and characterization of mixed ligand 2,2';6',2' '-terpyridine (tpy) ruthenium complexes with 2,6-bis([1,2,4]triazol-3-yl)pyridine, 2,6-bis(5-phenyl-[1,2,4]triazol-3-yl)pyridine, and 2,6-bis([1,2,3,4]tetrazol-5-yl)pyridine are reported. The species are characterized by HPLC, 1H NMR, UV/vis, and emission spectroscopy. The photophysical properties of the complexes are investigated as a function of temperature over the range 80-320 K. The emission lifetime observed for the fully deprotonated compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 68 publications
6
104
0
Order By: Relevance
“…Protonation of the amino group renders the tpy-NH 3 + ligand a weaker σ donor, thus decreasing the electron density at the metal centre and lowering the occupied metal-based orbitals. [12,40] Deprotonation of the COOH group of [2] 2+ shifts the unoccupied orbitals of the tpy-COO -ligand to higher energies. Further deprotonation (of the NH 2 group) renders the tpy-NH -ligand a better donor, increasing the energy of the occupied ruthenium orbitals and thus shifting the 1 MLCT absorption to lower energy.…”
Section: Design and Synthetic Strategymentioning
confidence: 99%
“…Protonation of the amino group renders the tpy-NH 3 + ligand a weaker σ donor, thus decreasing the electron density at the metal centre and lowering the occupied metal-based orbitals. [12,40] Deprotonation of the COOH group of [2] 2+ shifts the unoccupied orbitals of the tpy-COO -ligand to higher energies. Further deprotonation (of the NH 2 group) renders the tpy-NH -ligand a better donor, increasing the energy of the occupied ruthenium orbitals and thus shifting the 1 MLCT absorption to lower energy.…”
Section: Design and Synthetic Strategymentioning
confidence: 99%
“…(m-Cl)Cl(CO) 6 ], which represent (according to X-ray diffraction data) unusual examples of metal ± metal interaction; the tetrazolate anions in these complexes are bound in the tridentate bridging mode. 76 Similarly, the substitution of 5-(2-pyridyl)tetrazole and 2,6-bis(tetrazol-5-yl)pyridine for chlorine in the complexes RuL 2 Cl 2 (L is 2,2 H -bipyridine, 4,4 H -dimethyl-2,2 H -bipyridine) 51 and Ru(tpy)Cl 3 (tpy is 2,2 H : 6 H ,2 HH -terpyridine) 78 gave ruthenium-containing tetrazoles 62 and 63 in 55% ± 84% yields. The UVspectroscopic and electrochemical studies have shown that the introduction of a tetrazolyl group having strong s-donor properties into the Ru(tpy)Cl 3 complex results in destabilisation of the ground energy state and decreases the metal oxidation potential.…”
Section: Synthesis Of Metal Derivatives From Tetrazolesmentioning
confidence: 99%
“…This is also accompanied by a decrease in the emission energy and an increase in the luminescence time from 1 to 80 ns. 78 The 5-R-tetrazolate anion replaces the acetoxy group in 2-and 4-mercuriomethylquinolinium salts. The 1 H NMR characteristics of compounds 64 prepared in this way in 76% ± 96% yields indicate that only one N-isomer is formed in each case; however, the available data are insufficient for assigning the reaction products to either N(1)-or N(2)-isomeric tetrazoles.…”
Section: Synthesis Of Metal Derivatives From Tetrazolesmentioning
confidence: 99%
“…The photophysical properties of molecules can be tuned by the introduction of various substituents on the terpyridine ligand [7][8][9][10][11][12][13][14]. Electron-withdrawing groups stabilize the lowest unoccupied molecular orbital (LUMO), while electron-donating groups destabilize the highest occupied molecular orbital (HOMO) [15].…”
Section: Introductionmentioning
confidence: 99%